Effects of Polysaccharide-Based Edible Coatings on Quality and Antioxidant Enzyme System of Strawberry during Cold Storage. (11th December 2017) - Li, Li; Sun, Jian; Gao, Haiyan; Shen, Yingbin; Li, Changbao; Yi, Ping; He, Xuemei; Ling, Dongning; Sheng, Jinfeng; Li, Jiemin; Liu, Guoming; Zheng, Fengjin; et al.
Abstract : Strawberry is a nutritious, but highly perishable fruit. Three polysaccharide-based edible coatings (alginate, chitosan, and pullulan) were applied to postharvest strawberry fruit during cold storage (4°C), and their effects on fruit quality and antioxidant enzyme system were investigated in the present study. The results showed that polysaccharide coatings showed a significant delay in fruit softening and rot and reduced changes in total soluble solid and titratable acidity content during 16 d storage. Polysaccharide coatings also maintained higher ascorbic acid and total phenolic contents than control from day 2 and significantly inhibited fruit decay and respiration after 12 d storage (p < 0.05 ). Polysaccharide treatments enhanced the activities of antioxidant enzymes (peroxidase, catalase, superoxide dismutase, and ascorbate peroxidase) so as to prevent lipid peroxidation and reduce membrane damage. Additionally, chitosan coating had the most positive effects on fruit quality amongst three polysaccharide-based edible coatings and presented the highest relative activities of antioxidant enzymes. These results indicated that polysaccharide-based edible coatings were helpful in postharvest quality maintenance of strawberry fruit.